Abnormal Development of Lung Innervation in Experimental Esophageal Atresia - Liu, X.M.; Aras-Lopez, R.; Martinez, L.; Tovar, J.A. (European Journal of Pediatric Surgery, 2012)
Background/Aim Patients with esophageal atresia and tracheo-esophageal fistula (EA-TEF) have chronic respiratory tract disease and deficient tracheal innervation. This study tests the hypothesis in rats with EA-TEF that deficient lung innervation could be one of the causes of respiratory disease.Material and Methods Pregnant rats were treated with either 2 mg/kg i.p. adriamycin or vehicle on E7, E8 and E9. Lungs and tracheas were retrieved on E15, E18 and E21 (term: E22). Innervation was examined by regular (PGP 9.5 and GDNF) and whole-mount (PGP 9.5 and α-actin) immunohistochemistry. PGP 9.5 and GDNF mRNA were measured by real-time, quantitative RT-PCR and the levels of PGP 9.5 protein by immunoblot. Embryonic lung primordia harvested on E13 were cultured for 72 h and airway peristalsis was assessed under an inverted microscope. PGP 9.5 expression was then examined in explants by whole-mount immunohistochemistry and RT-PCR. Values were compared with non-parametric tests.Results Neural networks were present in both EA-TEF and control fetuses on E15, E18 and E21, but the neural network was obviously disorganized in whole-mount immunohistochemistry of EA-TEF. The pan-neural marker PGP 9.5 protein was increased at term whereas the neural chemo-attractant GDNF protein was unchanged. PGP 9.5 mRNA significantly increased from subnormal levels on E15 to very increased ones on E18 compared with controls. GDNF mRNA levels followed the same trend. Airway peristalsis of explanted embryonal lungs was similar in both groups. The neural networks were underdeveloped in these primordia, as assessed by whole-mount PGP 9.5 immunohistochemistry and RT-PCR.Conclusions The development of respiratory tract innervation in adriamycin-induced EA-TEF was delayed and abnormally controlled in rats compared with controls. However, these deficiencies were apparently compensated for at term and had no effect on airway peristalsis. The possible significance of innervation anomalies for respiratory sequelae in EA-TEF patients deserves further investigation.
Keywords: tracheo-bronchial; lung; innervation; esophageal atresia; tracheo-esophageal fistula